PREVENTION OF PURULENT-SEPTIC COMPLICATIONS DURING LAPAROSCOPIC SURGERIES ON PELVIC ORGANS WITH THE RISK OF VAGINAL MICROBIOTA CONTAMINATION - Zaporozhan, V.M.; Gladchuk, I.Z.; Rozhkovska, N.M.; Volyanska, A.G.; Shevchenko, O.I.; Kushnir, H.Yu. (World of Medicine and Biology, 2020)
The efficacy analysis of the purulent-septic complications prevention at 115 “clean-contaminated” laparoscopic surgeries on the pelvic organs (laparoscopic hysterectomy, conservative myomectomy with the node resection via colpotomy incision) was performed. In the experimental group of patients (n = 60), 0.02% decamethoxin solution was administered intravaginally. The control group (n = 55) received traditional systemic perioperative antibiotic prevention using cephalosporins. It was shown that the early postoperative period dynamics, as well as indicators of systemic inflammatory response and the number of complications did not show significant differences between the studied groups, and in the experimental group there was an increase in the lactobacilli number and 87.3% decrease in the opportunistic pathogens content, which indicated the feasibility of preventive intraoperative topical decamethoxin application.
Keywords: laparoscopy; purulent-septic complications; prevention; decamethoxin